Dynamics of Internalizing Muslim Dress: A Study on the Gap Between Formal Compliance and Religious ConsciousnessStudents of Al-Husniyah Islamic High School - Deddy Yusuf Yudhyarta; Faridatul Munawaroh; Zulkarnainsyah Zulkarnainsyah; Nur’aini Gusasfian (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
the obligation to wear Muslim attire in islamic educational institution is intendied not only as a form of compliance with regulations but also as an effort to internalize Sharia value. This study aims to analyze the internatinaliization of the obligation to wear Musli attire at SMA Islam Al Husniyah Pulau Kijang accross the aspects of understanding acceptance, and practice. using a descrioetive qualitative approach supported by qualitative data this research invoiled 58 female students a respondents selected through a total sampling technique. Data were collected via questionairess, interviews, and documen, then analyzed using descrptive percentages and thematic interpretation. The results indicate that internalization is the